Examining Approach and Avoidance Valences of the 3 X 2 Achievement Goal Types on an Engineering Student Sample: A Validity Approach - Hunsu, Nathaniel; Oje, Adurangba V.; Jackson, Andrew; Olaogun, Olanrewaju Paul (Frontiers in Psychology, 2021)
Development of the 3 X 2 Achievement Goal Questionnaire (AGQ) advanced approach and avoidance goals in three goal types within the achievement goal framework: task-, self-, and other-based. The purpose of the present study was to examine empirical support for the construct validity, reliability, and measurement invariance of factors on the questionnaire and compare model fit of the 3 X 2 configuration to other alternatives. In addition to validating some of the findings reported in earlier studies, especially the inclusion of task-based goal orientations, the study highlights a limitation and potential boundary of the 3 X 2 achievement goal questionnaire. While the 3 X 2 model was found to be structurally valid, we found multiple validity supports for a definition-based model of the AGQ scale, which does not differentiate between goal approach or avoidance. The study provides some indications that approach and avoidance goals can be indistinguishable to some respondents. Nonetheless, the scale was invariant across multiple groups making group comparison possible.